PENGARUH PEMBANGUNAN PERUMAHAN TERHADAP PERKEMBANGAN WILAYAH KABUPATEN JAYAWIJAYA - Adrianus Huby; Risky Novan Ngutra; Thobby Wakarwamu (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2022)
The need for property is currently increasing in line with the needs and purchasing power of the community. The increase in settlements is thus related to housing prices in accordance with community demand. This study aims to analyze the development of housing development in Jayawijaya Regency. The results of the study show that: (1) Development of Housing Development in Jayawijaya Regency in 2016-2020, namely the area of Jayawijaya Regency is 8,496 km. Where in 2016 an area of 450.1 Ha, increased to 496.8 Ha in 2020. This caused a reduction in residential land from an area of 637.94 Ha in 2016 and to 591.24 Ha in 2020. This means that the development of housing development has an impact on reducing residential area in Jayawijaya Regency. (2) Housing development has an effect on the development of the Jayawijaya Regency area as evidenced by a significant value <0.05. In addition, the development of changes has a 100% influence on regional development in Jayawijaya Regency. Then also the direction of the positive relationship means that as housing development increases, the development of housing and settlement areas in Jayawijaya district will also increase.